Analisis Teknik Dasar Dribbling Peserta Sepakbola Klub Putra FC Mardiharjo Kecamatan Purwodadi Kabupaten Musi Rawas - Fajar Ade Nata; Azizil Fikri; Wawan Syafutra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the basic dribbling techniques of the participants of the Men's football club FC Mardiharjo, Purwodadi District, Musi Rawas Regency. This study used the descriptive qualitative method. The subjects of this study were 20 people who joined the football club at FC Mardiharjo Men's Club, Purwodadi District, Musi Rawas Regency. The data analysis technique used is data collection, data reduction, data presentation, and data verification. Test the validity of the data using a credibility test which is done by means of triangulation. The results showed that the basic dribbling techniques carried out by the participants of the FC Mardiharjo Men's football club could be in a good category at 67%. In conclusion, the essential technical skills of dribbling and passing in football club participants are in the sufficient category Keywords: Analysis, Basic Technical Skills, Dribbling,